Broadband single-molecule fluorescence enhancement based on self-assembled Ag@Au dimer plasmonic nanoantennas. Issue 47 (1st November 2022) - Lin, Yunpeng; Hu, Jinyong; Zhang, Wenbo; Jiang, Li; Yi, Deqi; Rujiralai, Thitima; Ma, Jie
Abstract : A self-assembled dimer nanoantenna features a single dye in its hotspot. Such Ag@Au dimer nanoantennas can yield a broadband single-molecule fluorescence enhancement over almost the whole visible spectrum and remain stable for more than one month. Abstract : Dimer optical antennas (OAs) enable great fluorescence enhancement and excitation volume reduction and hence potentially can be a very useful tool for single-molecule detection. The realization of broadband fluorescence enhancement with a dimer OA remains an essential step for its usage in multi-color single-molecule fluorescence (SMF) detection. Although silver dimer OAs have been shown to be able to yield broadband fluorescence enhancement over the visible spectrum, they are amenable to oxidization, hard to functionalize, and could cause cytotoxicity. To overcome these limitations, in this work, we took advantage of nano-sized silver due to its optical properties and gold due to its chemical properties and developed an ameliorated Ag@Au dimer OA in terms of its overall performance. The Ag@Au nanoparticle in the dimer OA contains a 70 nm silver core and an ultra-thin (∼1–5 nm) gold shell which play a key role in its optical responses. Furthermore, we employed three typical dyes, i.e., FAM, TAMRA and Cy5, representing the blue, yellow and red ranges, respectively, and characterized their single-molecule fluorescence enhancements in the presence of Au or Ag@Au OAs. Our results indicate that, in contrast to its Au counterpart, the Ag@Au dimer OA prepared here can greatly improve its optical response in the blue range and eventually achieve broadband fluorescence enhancement throughout almost the whole visible spectral range. Meanwhile, it also maintains good chemical stability and accessibility to functionalization. Such Ag@Au dimer OAs are thus expected to have many important applications in the future, including single-molecule sequencing and multi-color biosensing.